Exergoeconomic and Thermodynamic Analyses of Solar Power Tower Based Novel Combined Helium Brayton Cycle‐Transcritical CO2 Cycle for Carbon Free Power Generation - Yunis Khan; Deepak Singh; Hakan Caliskan; Hiki Hong (Global Challenges, 2023)
Abstract In the present study, a novel combined power cycle for solar power tower (SPT) system consisting of helium Brayton cycle (HBC) and transcritical CO2 (TCO2) for waste heat recovery is being studied for carbon‐free generation. The performance of the proposed SPT based combined cycle (SPT‐HBC‐TCO2 cycle) is compared with SPT based basic cycle (SPT‐HBC) based on exergoeconomic and thermodynamic analyses. It is concluded that the SPT‐based combined cycle (SPT‐HBC‐TCO2 cycle) produces a thermal efficiency of 32.39% and exergy efficiency of 34.68% with an electricity cost of 1.613 UScent kWh−1. The exergy and thermal efficiency of the SPT‐based combined cycle are enhanced by 13.18% and 13.21% respectively, while electricity cost is reduced by around 2% as compared to the SPT‐based basic cycle (SPT‐HBC) configuration at base conditions. A notable finding is that, despite the additional expenditures related to the bottoming cycle, the cost of electricity is lesser for the proposed combined cycle. Additionally, a comparison with the related prior published research exhibits that the performance of the current novel system is superior to that of the systems based on steam rankine cycle and supercritical CO2 cycles.